Butterfly (Lepidoptera: Papilionoidae) diversity and structure community in Lumajang, East Java, Indonesia - NAJMATUL MILLAH; AMIN SETYO LEKSONO; BAGIO YANUWIADI (Nusantara Bioscience, 2023)
Abstract. Millah N, Leksono AS, Yanuwiadi B. 2023. Butterfly (Lepidoptera: Papilionoidae) diversity and structure community in Lumajang, East Java, Indonesia. Nusantara Bioscience 15: 118-128. Lumajang is one of the district in East Java, Indonesia with an area of around 1,790.90 km2 with various ecosystems. Unfortunately, several ecosystems in Lumajang have been degraded, affecting biodiversity, especially butterflies. The aim of this study was to analyze the structure of butterfly communities in Lumajang and analyze the species as bioindicators. The study was conducted in 5 habitats: Village, Agriculture, City Park, Community Forest, and Conservation Forest. The butterfly sampling method in this study was an Active Visual Survey using the Transect Pollard Walk; environmental factors were also measured during the study (temperature, humidity, light intensity, wind velocity, and altitude). The butterfly diversity and the measurement of environmental factors were analyzed for correlation using the Principal Component Analysis (PCA). The results of the study consisted of 124 species. Several were endemic species (Cyrestis lutea (Zincken, 1831), Ypthima nigricans (Snellen, 1892), Parantica albata (Zincken, 1831), Mycalesis sudra (Felder, 1867), and Pachliopta adamas (Zincken, 1831)), then protected species (Troides helena (Linnaeus, 1758), Troides cuneifera (Oberthür, 1879), and Troides amphrysus (Cramer, 1779)). The Shannon-Wienner diversity index values from highest to lowest are Community Forest (3.52), Conservation Forest (3.32), City Park (2.98), Village (2.79), and Agriculture (2.29). The results can be used as basic data and are expected to support butterfly conservation strategies in Indonesia, especially in Lumajang, East Java, Indonesia.